Nutrient Analysis of Selected Wild Edible Mushrooms Collected from Thulo Ban Community Forest, Myagdi District, Nepal - Shrestha, Shashi; Thapa, Sadikshya; Jha, Sanjay Kumar (Journal of Plant Resources, 2023)
The study analyzes the nutrient content of three wild edible mushrooms Cantharellus cibarius, Laccaria laccata and Scleroderma cepa commonly consumed by the local people of Arjam, Myagdi district. Thirteen parameters were analyzed such as ash, carbohydrate, fat, moisture, protein, manganese, zinc, magnesium, potassium, iron, copper, phosphorus and calcium. The test methods used for ash, fat, moisture, protein and phosphorous content were ignition, soxhlet extraction, oven dry method, kjeldahl digestion method and spectrophotometric method respectively. Carbohydrate content was determined by calculation method and iron, manganese, copper, zinc, calcium, magnesium and potassium content estimation were done by AAS method. All macro and micronutrient compositions were determined on a dry weight basis. Ash, carbohydrate, fat, moisture and protein are ranges from 7.05-13.38%, 61.89-71.37%, 0.78-1.94%, 12.37-13.66% and 16.18-24.47% respectively, whereas calcium, magnesium, phosphorus and potassium ranges from 0.13-0.15 µg/g, 0.09-0.11µg/g, 0.25-0.37 µg/g and 1.41-3.40 µg/g respectively. Similarly copper, iron, manganese and zinc ranges from 2.40-30.94 µg/g, 0.08-0.20 µg/g, 7.22-16.06 µg/g and 45.70-77.35 µg/g respectively.